Tradisi Ogoh-Ogoh Sebagai Sarana Kerukunan Antar Umat Beragama di Desa Gunung Sari, Kab. Kolaka - Sari, Patma; Sulastry, Helda; Marani, Irgi Prasetyo; Biringkaka, Wahida; Nilam, Nilam; Alam, Husaema; Iqbal, Muhd.; Alim, Sahrul; Mawarni, Ayu; Fairin, Muh.; Era, Emon Eru (Penerbit Widina, Widina Media Utama, 2025)
The Ogoh-ogoh tradition in Gunung Sari Village, Watubangga District, Kolaka Regency, has been carried out since 1982 as part of preparations for the Hindu New Year celebration of Nyepi. Although the majority of the village's population is Muslim, this tradition remains alive as a symbol of cleansing from evil through the burning of large, terrifying effigies. This research examines the development of this tradition and its alignment with the village's regulations. The aim of this research is to describe the implementation of the Ogoh-ogoh tradition, analyze the symbolic meaning within the tradition, and evaluate whether the tradition complies with local government regulations. Additionally, this research seeks to identify the factors that support the continuation of this tradition within a predominantly Muslim community. The research method used is qualitative with an ethnographic approach. Data was collected through interviews with community leaders and other key informants, as well as related literature. The collected data was analyzed descriptively to understand the implementation of the tradition. The Ogoh-ogoh tradition is embraced with enthusiasm and does not conflict with village regulations. This tradition is maintained as a form of respect for cultural and religious diversity. The Ogoh-ogoh tradition in Gunung Sari Village reflects interfaith harmony and can be carried out without conflict with village rules.ABSTRAKTradisi Ogoh-ogoh di Desa Gunung Sari, Kecamatan Watubangga, Kabupaten Kolaka, dilaksanakan sejak 1982 dan menjadi bagian dari persiapan Hari Raya Nyepi umat Hindu. Meskipun mayoritas penduduk desa beragama Islam, tradisi ini tetap hidup sebagai simbol pembersihan dari keburukan melalui pembakaran patung raksasa. Penelitian ini mengkaji perkembangan tradisi ini serta kesesuaiannya dengan peraturan desa setempat. Penelitian ini bertujuan untuk menggambarkan pelaksanaan Tradisi Ogoh-ogoh, menganalisis makna simbolis dalam tradisi ini, serta mengevaluasi apakah tradisi tersebut sesuai dengan peraturan pemerintah desa. Selain itu, penelitian ini ingin mengidentifikasi faktor yang mendukung kelangsungan tradisi tersebut dalam konteks masyarakat yang mayoritas Muslim. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan etnografi. Data dikumpulkan melalui wawancara dengan tokoh masyarakat dan informan kunci lainnya, serta literatur terkait. Data yang terkumpul dianalisis secara deskriptif untuk memahami pelaksanaan tradisi. Tradisi Ogoh-ogoh diterima dengan antusiasme dan tidak bertentangan dengan peraturan desa. Tradisi ini dijaga sebagai bentuk penghormatan terhadap keberagaman budaya dan agama. Tradisi Ogoh-ogoh di Desa Gunung Sari mencerminkan kerukunan antaragama dan dapat dilaksanakan tanpa konflik dengan aturan desa.